Does asymmetry in the stomatognathic system correlate with body posture impairments? A systematic review - Dal Borgo, Beatrice; Perinetti, Giuseppe; Contardo, Luca (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
Objectives: To assess the potential correlations between anatomical and functional asymmetry in the stomatognathic system and bodyposture impairments. Methods: Literature search using the Medline, SCOPUS, LILACS and SciELO databases, the Cochrane Library and a manual search.Experimental and observational studies were included with no restrictions as to the type of asymmetry. Type of asymmetry, treatment and/or recording conditions, follow-up, postural examinations, main results and clinical implication were extracted, and risk of bias was assessed. Results: Eleven articles (including one randomized clinical trial) were retrieved. The risk of bias was medium in 6 studies and high inthe remaining investigations. Only three studies, all with a high risk of bias and without follow-up, reported significant correlations between the asymmetry in the stomatognathic system and body posture impairments. Discussion: According to the limited present evidence, asymmetry in the stomatognathic system does not appear to correlate withbody posture impairments at a clinically relevant level.